Kajian Infografis Poster Bahaya Narkoba BNN - Wulandari, Wulandari (Magenta | Official Journal STMK Trisakti, 2017)
Information becomes very important for the society. Each day they are faced with a variety and variations of form of information. Starting from the information in the field of academics, marketing, editorial and so forth. The need for effective information sharing with an attractive view makes a presentation of information appear. Infographics become one form of information distribution that has begun to develop. Infographics bring enlightenment in displaying data - data in the form of text and numbers into a display that appeals to readers. Infographics also become one of the solutions in conveying information in the form of posters or e-posters.